The Use of Social Media by The Indonesian Council of Ulama (MUI) in Mandailing Natal District to Build Religious Awareness and Community Solidarity - Farid, Ahmad Salman (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to analyze the use of social media by the Indonesian Council of Ulama (MUI) in Mandailing Natal District in building religious awareness and community solidarity. In the current digital era and globalization of information, social media has become an important communication tool to achieve this goal. This study uses a qualitative approach interviews with MUI members, direct observation, and analysis of MUI social media content in Mandailing Natal District. The results of the study show that the Mandailing Natal District MUI has actively utilized social media in an effort to build religious awareness and community solidarity. MUI uses various social media platforms such as Twitter, Instagram and TikTok to convey religious messages, fatwas, announcements and information related to religious activities. These contents cover various topics such as religious teachings, morality, worship, and social to Muslims.Keywords : Indonesian Indonesian Council of Ulama, social media, religious awareness, people's solidarity, Mandailing Natal District